Knowledge, Attitudes, and Practices of Medical Students Regarding COVID-19 in Afghanistan: A Cross-Sectional Study - Nemat A; Raufi N; Sediqi MF; Rasib AR; Asady A (Dove Medical Press, 2021)
Arash Nemat,1,2 Nahid Raufi,3,4 Mohammad Faiq Sediqi,5 Aziz Rahman Rasib,6 Abdullah Asady1 1Department of Microbiology, Kabul University of Medical Sciences, Kabul, Afghanistan; 2Department of Cardiology, Nanfang Hospital, Southern Medical University, Guangzhou, People’s Republic of China; 3Department of Dermatology, Kabul University of Medical Sciences, Kabul, Afghanistan; 4Department of Dermatology, Guangdong Provincial Dermatology Hospital, Southern Medical University, Guangzhou, People’s Republic of China; 5Department of Histology, Kabul University of Medical Sciences, Kabul, Afghanistan; 6Department of Neuropsychiatry, Kabul University of Medical Sciences, Kabul, AfghanistanCorrespondence: Arash NematDepartment of Microbiology, Kabul University of Medical Sciences, Jamaal Mina, Kabul, 1001, AfghanistanTel +93 706 717 987Email dr.arashnemat@yahoo.comBackground: The coronavirus pandemic has had devastating effects on many nations, including Afghanistan. Public awareness and following recommendations play an important part in managing such a large-scale crisis, which are affected largely by knowledge, attitudes, and practices (KAP). Medical students can act as reliable sources of information for the public in such a scenario. This study aimed to investigate KAP of medical students regarding COVID-19.Methods: A cross-sectional online survey was conducted in October 2020 among medical students in Afghanistan, Kabul University of Medical Sciences. Information on sociodemographics and KAP, was collected using a web-based questionnaire.Results: A total of 1,169 medical students completed the survey. More than half were female (54.6%), a majority (95%) aged ≥ 20 years, and more than half (56.2%) lived in the city of Kabul. Overall, students had acceptable KAP regarding COVID-19, except for a few undesirable responses with regard to the risks of close contact with COVID-19 patients, incubation periods, and groups vulnerable to COVID-19.Conclusion: Overall, the students had acceptable KAP regarding COVID-19, except for the few undesired aforementioned responses, which need more focus during awareness campaigns in future.Keywords: SARS-COV2, pandemic, surveys and questionnaires, public health